Ambitions and realities: Are Global Fund investments designed to achieve resilient and sustainable systems for health? Findings from the Global Fund Prospective Country Evaluation. - Nicole Salisbury; Saira Nawaz; Justine Abenaitwe; Audrey Batzel; Emily Grapa; Francisco Rios Casas; Virginia Cerezo; Matthew Cooper; Herbert C Duber; Ibrahima Gaye; Bernardo Hernandez; Constant Kingongo; et al. (PLOS Global Public Health)
Strengthening resilient and sustainable systems for health (RSSH) is central to the Global Fund's strategy, however questions persist about the Global Fund's role in the health systems strengthening space, and the extent to which investments are designed to achieve strengthening objectives, or just fill in gaps in the system. This paper reports on findings from the Prospective Country Evaluations (PCE), a multi-country multi-year evaluation of Global Fund support. We adapted a framework from Chee et al. (2013) to assess whether Global Fund investments were designed to strengthen or support the health system. Per this framework, 'systems support' refers to improvements in health systems functioning primarily driven by increases in inputs, whereas 'systems strengthening' refers to activities that drive changes in how the health system operates (often related to policies, regulations, governance structures, behavior change, and resource optimization). In the 2017 and 2019 funding cycles, we found that despite calls from the Global Fund to invest more strategically to strengthen health systems, a high proportion of RSSH funding was directed toward activities that support the health system. Factors underlying this pattern include limitations imposed by the three-year grant cycle, a lack of clear guidance on how to design strengthening investments, a persistent need for funding to address input gaps, and minimal feedback during the funding request process related to RSSH design. For the Global Fund, and indeed other global health initiatives, to contribute to sustained strengthening of health systems, is likely to require enhanced guidance and technical assistance, as well as improved measurement of outputs and outcomes.